2020
DOI: 10.1038/s42003-020-01443-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing calmodulin binding to cardiac ryanodine receptor completely inhibits pressure-overload induced hypertrophic signaling

Abstract: Cardiac hypertrophy is a well-known major risk factor for poor prognosis in patients with cardiovascular diseases. Dysregulation of intracellular Ca2+ is involved in the pathogenesis of cardiac hypertrophy. However, the precise mechanism underlying cardiac hypertrophy remains elusive. Here, we investigate whether pressure-overload induced hypertrophy can be induced by destabilization of cardiac ryanodine receptor (RyR2) through calmodulin (CaM) dissociation and subsequent Ca2+ leakage, and whether it can be ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In brief, total RNA was extracted from TY10 cells using the RNeasy Mini Kit (Qiagen), and messenger RNA was purified as described previously. 20 Complementary DNA libraries were produced using a NEBNext Ultra II RNA Library Prep kit (New England Biolabs) and NEBNextplex Oligos for Illumina, as described previously. 20 In this approach, messenger RNA was fragmented in NEBNext First Strand Synthesis Reaction Buffer at 94°C for 15 minutes in the presence of NEBNext Random Primers and was reverse transcribed with NEBNext Strand Synthesis Enzyme Mix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In brief, total RNA was extracted from TY10 cells using the RNeasy Mini Kit (Qiagen), and messenger RNA was purified as described previously. 20 Complementary DNA libraries were produced using a NEBNext Ultra II RNA Library Prep kit (New England Biolabs) and NEBNextplex Oligos for Illumina, as described previously. 20 In this approach, messenger RNA was fragmented in NEBNext First Strand Synthesis Reaction Buffer at 94°C for 15 minutes in the presence of NEBNext Random Primers and was reverse transcribed with NEBNext Strand Synthesis Enzyme Mix.…”
Section: Methodsmentioning
confidence: 99%
“… 20 Complementary DNA libraries were produced using a NEBNext Ultra II RNA Library Prep kit (New England Biolabs) and NEBNextplex Oligos for Illumina, as described previously. 20 In this approach, messenger RNA was fragmented in NEBNext First Strand Synthesis Reaction Buffer at 94°C for 15 minutes in the presence of NEBNext Random Primers and was reverse transcribed with NEBNext Strand Synthesis Enzyme Mix. The library fragments were then concentrated, and index sequences were inserted during polymerase chain reaction amplification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from the fibroblasts or LSE using the RNeasy Mini Kit (Qiagen, Hilden, Germany), and mRNA was purified with oligo dT beads (NEBNext Poly (A) mRNA magnet Isolation Module, New England Biolabs, NEB, Ipswich, MA). The procedure of the complementary DNA (cDNA) libraries was carried out with NEBNext Ultra II RNA library Prep kit (NEB) and NEBNextplex Oligos for Illumina following a previously described method (Kohno et al, 2020).…”
Section: Whole Transcriptome Analysis With Rna-seqmentioning
confidence: 99%
“…In our previous study, we reported that RyR2 V3599K KI mice, in which the calmodulin (CaM) binding domain of the myocardial ryanodine receptor (RyR2) was mutated to enhance the affinity of CaM to RyR2 [ 5 ], do not develop cardiac hypertrophy in the transverse aortic coarctation (TAC) model [ 6 ]. In this model, LV systolic and diastolic function is maintained without LV hypertrophy, even when the LV peak pressure is increased in WT mice.…”
Section: Introductionmentioning
confidence: 99%